Informed consent during the intrapartum period: an observational study of the interactions between health professionals and women in labour involving consent to procedures - Marshall, Jayne E. (2005)
This ethnographic study using participant observation, aimed to explore the issue of informed consent to procedures undertaken during the intrapartum period. It involved recruiting 100 healthy women, who went into labour spontaneously at term, at the point they were admitted to the labour ward. The data collection took place in a large teaching hospital in an East Midlands city from April 1997 until December 1999. The subjects (health professionals and women) were observed throughout the labour until the woman and baby were transferred to the postnatal area. Follow-up interviews were conducted with the woman and midwives, within 24 hours, using a semi-structured format based on the observations.